STUDY ON CHARACTERIZATION OF Ni/BIOCHAR CATALYST DERIVED FROM MICROALGAL BIOMASS - Pham, Vuong Van; Nguyen, Hong Khanh Dieu (Vietnam Journal of Science and Technology, 2016)
Biochar supported nickel (Ni/biochar) catalyst was prepared by incipient wetness method and characterized by using a series of techniques such as XRD, SEM, TEM, FT-IR, H2-TPR and BET. These charaterizations indicated the catalyst structure and demonstrated its potential for applications in reduction – oxidation reactions in particular the HDO process.